2009
DOI: 10.1007/s00520-009-0707-2
|View full text |Cite
|
Sign up to set email alerts
|

Is bra discomfort a barrier to exercise for breast cancer patients?

Abstract: Goals of work Although exercise can provide a range of benefits for women living with a breast cancer diagnosis, many impediments to exercise exist. Several psychosocial and physical capacity impediments to exercise have been investigated, but no study has systematically investigated whether bras impede breast cancer patients from exercising. This study aimed to assess the extent to which exerciseinduced breast pain and bra discomfort were reported by women living with breast cancer and whether this breast pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 29 publications
2
26
1
Order By: Relevance
“…Therefore, to encourage exercise participation among breast cancer survivors, these barriers to exercise need to be identified and minimised or removed [3]. In a recent study investigating 19 potential barriers to exercise, a lack of discipline, procrastination, being fatigued by exercise, and not being able to find a comfortable bra to exercise in, were ranked as the top four barriers to exercise by women treated for breast cancer [10]. Of these 19 barriers, bra discomfort is the highest ranked barrier that can be modified through an external intervention, such as by providing exercise bras that suit the needs of breast cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to encourage exercise participation among breast cancer survivors, these barriers to exercise need to be identified and minimised or removed [3]. In a recent study investigating 19 potential barriers to exercise, a lack of discipline, procrastination, being fatigued by exercise, and not being able to find a comfortable bra to exercise in, were ranked as the top four barriers to exercise by women treated for breast cancer [10]. Of these 19 barriers, bra discomfort is the highest ranked barrier that can be modified through an external intervention, such as by providing exercise bras that suit the needs of breast cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, only one other study could be located which investigated the impact of bra discomfort on exercise levels among breast cancer survivors [10]. In that study, a significant proportion of respondents (70%) experienced exercise bra discomfort, although this was not related to weekly exercise levels or reported physical side effects.…”
Section: Introductionmentioning
confidence: 99%
“…The limitation of these studies is that results from these studies could only be applied to patients who are participating in regular or scheduled exercise sessions. Meanwhile, other studies, including our current study, on exercise barriers perceived in a typical day used different questionnaires Perna et al, 2008;Rogers et al, 2008;Gho et al, 2010;Loh et al, 2011). Therefore, the results should be carefully interpreted, taking study method and assessment tools into account.…”
Section: Discussionmentioning
confidence: 88%
“…Several studies have been conducted to explore the barriers that keep cancer patients from participating in exercise, including breast (Nelson, 1991;Leddy, 1997;Rogers et al, 2006;Rogers et al, 2007;Courneya et al, 2008;Gho et al, 2010;Loh et al, 2012;Ottenbacher et al, 2013), prostate (Ottenbacher et al, 2013), and head and neck (Rogers et al, 2008) cancer. For colorectal cancer, Courneya et al (2005) identified exercise barriers during an exercise program intervention and Lynch et al (2010) reported barriers to physical activity for colorectal cancer patients according to the time period after diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The online survey instrument was based on a previously validated paper-based questionnaire [19]. To validate the online version, seven focus groups with breast cancer patients were conducted (total participants = 20) at community centers around the greater Sydney area.…”
Section: Online Survey Instrumentmentioning
confidence: 99%